Accuracy of the intra-operative radioauided localization of the sentinel lymph node (SLN) 24 hours after lymphoscintigraphy in patients with malignant melanoma - Kropp, J.; Stein, A.; Hackert, I.; Sebastian, G.; Meurer, M.; Griming, T.; Liepe, K.; Pinkert, J.; Franke, W.-G. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: For optimized logistics for the sentinel lymph-adenectomy (SL) it might be helpful for the clinics involved if a longer time period between the lymphoscintigraphy (LS) and surgery is possible. Therefore, we investigated if a precise localization of the sentinel lymph node is possible 24 hours after LS. Methods: 78 patients with primary malignant melanoma (MM; η = 44) or with MM pre-operated by excisional biopsy (n = 34) were investigated. In 40 cases the tumor was localized on the trunk and in 38 cases on the extremities. Mean MM thickness was 2.68 mm (range: 0.29 to 12 mm). In all patients a lymphoscintigraphy (LS) with an average of 85 MBq of Tc-99m nanocolloid was performed one day prior to surgery. Immediately after tracer application dynamic data acquisition was started at a LFOV gamma camera followed by a whole body scan. With a hand-held gamma detector (C-Trak®) 2,4,6,8, and 24 hours after tracer administration the SLN was identified and the counts registered. Results: 94 SLNs were identified in 87 lymphatic basins from which 86 could be resected. Nine MM showed two draining channels. After 24 hours 15.5% (as an average) of the initial counts could be measured in the SLN. The uptake in the SLN in pre-operated versus patients with primary tumor was statistically not significant (p = 0.4). In 16 cases (20.5%) the SLN was tumor positive. Four of those patients developed distant metastases and two died within the first year. None of the patients with negative SLN developed distant metastases or died. Conclusion: The remaining activity in the SLN up to 24 hours after administration is sufficient for their intra operative localization. The method of lymphoscintigraphy and localization of the SLN by a hand-held gamma detector optimizes the intra operative identification of the SLN in patients with malignant melanoma.
Keywords: Melanoma; sentinel lymph node; gamma probe; lymphoscintigraphy; technetium nanocolloids